Silica Tethered Ruthenium Catalyst for the Hydrogenation of CO2 Gas - R. Upadhyay, Praveenkumar; Srivastava, Vivek (Letters in Organic Chemistry, 2016)
Background: In recent years CO2 utilization and conversion of CO2 into the value added chemicals have attracted great attention of leading research groups. However, CO2 is widely accepted as reagent for the synthesis of carbonates and other important chemicals such as methanol, aspirin, formic acid etc, but CO2 reduction is still a major challenge for the scientific community as they are extremely thermodynamically stable. In this report, we are offering the synthesis of silica-tethered ruthenium catalyst (SRUC) for the hydrogenation of CO2 to formic acid. Methods: The SIRUC catalytic system was synthesized by a multistep grafting process using iminophophine ligand tethered to mesoporus SBA-15 inorganic support. After activating the SRUC catalyst with hydrogen gas, it was applied as hydrogenating catalyst for CO2 gas. It is worth noted that, SBA-15 was synthesized as per reported protocol and the important IV- type isotherm was recorded while performing N2 physisorption analysis. Results: The catalytic efficiency of silica-tethered Ru catalysts was screened for the hydrogenation of CO2 to formic acid. The hydrogenation reaction was carried out in 100 mL autoclave with triethyl amine (NEt3) and water under the pressure of CO2 and hydrogen gas (40 bar, CO2: H2=1:1) at 75°C. The formation of formic acid (or formate) was calculated through 1H NMR. As per the experimental data, it was clearly observed that catalyst system only works effectively with phosphine ligands and offered the formic acid with significant TON/TOF value opposite to SRUC-4A catalytic system. Higher catalytic activity in terms of TON/TOF value was obtained with SRUC-1A material carries the bidentate phosphine ligand at 100°C. Conclusion: In this manuscript, we reported a new protocol to synthesize mesoporous silica-tethered Ru complexes (SRUC 1A-4A). Among these, materials, SRUC 1A was found and effective heterogeneous catalyst for the selective CO2 hydrogenation reaction to obtain formic acid under normal reaction condition. In terms of catalyst recycling, this catalytic system was found highly active in catalyst recycling test up to 6 cycles without any significant loss of TON value of formic acid. In parallel, we also performed the filtration experiment and the obtained results were found in good agreement with recycling test results.
Keywords: carbon sequestration